Penanaman Nilai Agama dan Spiritual Terhadap Anak Pendidikan Dasar - Aliyah Yaasin; Eryani Rosmawati Nur Hakim; Gusmaneli Gusmaneli (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Instilling religious and spiritual values ​​in children is a fundamental component in forming their character and social behavior. This article discusses various effective methods used by parents and teachers in educating children, including example, habituation, discussion, and the use of interactive media. By involving parents as the first educators and teachers as formal educators, an environment that supports the process of internalizing religious values ​​can be created. This research also highlights the positive impact of religious education on the development of children's behavior, such as increasing empathy, integrity and cooperative abilities. Even though there are challenges in the digital era, such as the influence of social media and limited parental time, collaboration between families, schools and communities is very necessary to ensure that religious and spiritual values ​​remain relevant and can be implemented in children's daily lives. Thus, it is hoped that holistic and integrated religious education can form a generation with noble and responsible morals.